2018
DOI: 10.1093/rap/rky043
|View full text |Cite
|
Sign up to set email alerts
|

Circulating PD-1+CXCR5−CD4+ T cells underlying the immunological mechanisms of IgG4-related disease

Abstract: Objective The aim was to study the pathological role of lymphocytes with a peripheral T helper-cell-like phenotype (PD-1 + CXCR5 − CD4 + ) in IgG4-related disease (IgG4-RD). Methods PD-1 + CXCR5 − CD4 + T cells in the blood of patients with IgG4-RD ( n = 53), patients with SS ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 19 publications
2
33
0
2
Order By: Relevance
“…30 Whereas previous studies indicated that these SLE parameters were highly correlated with the frequency of cTfh cells, 31 other studies indicated an even higher correlation with cTph cells than cTfh cells. 29 An increase in circulating Tph cells has also been observed in other autoimmune and inflammatory diseases, such as Sjögren's syndrome, 32 IgG4-related diseases (IgG4-RDs), 33,34 systemic sclerosis, 35 IgA nephropathy 36 and type I diabetes. 37 Some correlations were observed between the frequency of circulating Tph cells and disease activity and/or clinical parameters in these diseases.…”
Section: Circulating Tph Cells In Autoimmune Diseasesmentioning
confidence: 94%
“…30 Whereas previous studies indicated that these SLE parameters were highly correlated with the frequency of cTfh cells, 31 other studies indicated an even higher correlation with cTph cells than cTfh cells. 29 An increase in circulating Tph cells has also been observed in other autoimmune and inflammatory diseases, such as Sjögren's syndrome, 32 IgG4-related diseases (IgG4-RDs), 33,34 systemic sclerosis, 35 IgA nephropathy 36 and type I diabetes. 37 Some correlations were observed between the frequency of circulating Tph cells and disease activity and/or clinical parameters in these diseases.…”
Section: Circulating Tph Cells In Autoimmune Diseasesmentioning
confidence: 94%
“…Because fractalkine, which is a ligand of CX3CR1, is highly expressed by endothelial cells in submandibular glands of IgG4-DS (H. Yabe, R. Kamekura R, unpublished data), Tph cells might have a role in the initiation of inflammation and maintenance of chronic fibroinflammation in IgG4-RD, although influencing vascularities in the lesions [47]. Given that destructive inflammation is observed in IgG4-RD [Figure 1], our experimental evidence indicates that Tph-like (PD-1 + CXCR5 - CD4 + ) cells, which preferentially contain cytotoxic granules of GZMA, are responsible for such pathological changes in IgG4-RD [19 ▪▪ ]. In this study, we could not see abundant expression of IL21 mRNAs in Tph-like cells compared with those in Tfh cells from patients with IgG4-RD [19 ▪▪ ].…”
Section: Collaboration Of Tph Cells and Tfh Cells In The Formation Ofmentioning
confidence: 97%
“…In addition, Gu-Trantien et al [45] reported that CD4 + T cells with a Tph cell-like phenotype were found in breast cancer tissues and that they have a possible regulatory function in immune responses against tumor cells. Based on these observations, we have first reported a possible pathological role of Tph cells in IgG4-RD [19 ▪▪ ]. Our results have shown that circulating PD-1 + CXCR5 − cells (including PD-1 hi CXCR5 − cells, thus collectively named Tph-like cells here) were significantly increased within CD4 + T cells in patients with IgG4-RD compared to those in healthy volunteers.…”
Section: Tph Cellsmentioning
confidence: 99%
See 2 more Smart Citations